2013
DOI: 10.5194/acpd-13-29007-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The quasi 16-day wave in mesospheric water vapor during boreal winter 2011/2012

Abstract: Abstract. This study investigates the characteristics of the quasi 16-day wave in the mesosphere during boreal winter 2011/2012 using observations of water vapor from ground-based microwave radiometers and satellite data. The ground-based microwave radiometers are located in Seoul (South Korea, 37° N), Bern (Switzerland, 47° N) and Sodankylä (Finland, 67° N). The quasi 16-day wave is observed in the mesosphere at all three locations, while the dominant period increases with latitude from 15 days at Seoul to 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In recent years, studies on the correlation between SSWs and the quasi 16‐day wave have attracted more and more attention (Laskar et al, ; Pancheva et al, ; Scheiben et al, ; Vineeth et al, ). However, as mentioned in section , most of these studies are based on a single SSW event.…”
Section: Statistical Analysis Of the Quasi 16‐day Waves During Sswsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies on the correlation between SSWs and the quasi 16‐day wave have attracted more and more attention (Laskar et al, ; Pancheva et al, ; Scheiben et al, ; Vineeth et al, ). However, as mentioned in section , most of these studies are based on a single SSW event.…”
Section: Statistical Analysis Of the Quasi 16‐day Waves During Sswsmentioning
confidence: 99%
“…Their study revealed that the quasi 16‐day wave is enhanced in the equatorial mesopause temperature prior to the SSW and indicated that the quasi 16‐day wave can propagate from the equatorial stratosphere to the North Pole in about 1 month. Scheiben et al () investigated the characteristics of the quasi 16‐day wave in the mesosphere during boreal winter 2011/2012 using ground‐based microwave radiometer and satellite water vapor observations. They found decreased quasi 16‐day wave activity during the 2012 SSW.…”
Section: Introductionmentioning
confidence: 99%
“…In Studer et al (2012) the numerical structure of the band-pass filter was shown. Lately the filter has been used to investigate the impact of the 27-day solar rotation cycle on mesospheric water vapor (Lainer et al, 2016) and to analyze the quasi 16-day planetary wave during boreal winter (Scheiben et al, 2014). We follow the advice from Oppenheim et al (1989) and run the filter with a zero phase lag forward and backward along the measurement time series.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations of the quasi 2-day wave are found for instance in studies by Salby (1981a), Rodgers and Prata (1981) and Yue et al (2012), and more recently by Tschanz and Kämpfer (2015), who analyzed the 2-day wave signatures in Arctic middle-atmospheric water vapor measurements in conjunction with the occurrence of sudden stratospheric warmings. Characteristics of the 5-day wave were analyzed by Rosenlof and Thomas (1990), Wu et al (1994), Riggin et al (2006) and Belova et al (2008), and waves with even longer periods have been observed in the mesosphere and lower thermosphere (Forbes et al, 1995;McDonald et al, 2011;Scheiben et al, 2014;Rüfenacht et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the mesosphere H 2 O is photochemically stable for weeks (Brasseur and Solomon, 2006) and this circumstance is used to investigate middle atmospheric wave dynamics from ground-based observations (Scheiben et al, 2014;Tschanz and Kämpfer, 2015;Lainer et al, 2016Lainer et al, , 2017. In this study we present quite continuous observations of the Q2DW signature in middle atmospheric water vapor for 7 years (84 months) by the middle atmospheric water vapor radiometer MIAWARA at 7.46 • E).…”
Section: Introductionmentioning
confidence: 95%